Linking Developing Country Firms’ Relational Capital to Their Export Performance in Global Value Chains: The Moderating Role of Technological Turbulence - Chowdhury, Misbah Uddin; Sui, Sui; Morgan, Horatio M.; Li, Dandan (Journal of Comparative International Management)

(untitled) (Management Futures, 2024)
Global value chains (GVCs) involve globally dispersed activities among interdependent firms. They provide an avenue for developing country firms to improve their export performance. A dominant view is that they can accomplish this outcome with close or trusted relationships with more established GVC partners. However, other factors determine how much such relational capital translates into superior export performance. Drawing on an interfirm learning perspective, we explain why the export effects of developing country firms’ relational capital with GVC buyers and suppliers could depend on technological turbulence. We hypothesize a positive relationship between these firms’ export performance and their relational capital with GVC buyers and suppliers. But we expect technological turbulence to weaken this relationship. Based on a sample of 95 Bangladeshi firms in the ready-made garment industry, this quantitative analysis reports evidence that partially supports our predictions. Specifically, we find a positive relationship between these firms’ relational capital with GVC buyers and their export performance. In addition, the higher the technological turbulence, the weaker this relationship. Overall, this research adds to the theory and practice of interfirm learning in GVCs from the perspective of developing country firms.